The Problem of Messiah in the Mind of Semitic Religion - Pangeran Manurung (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2018)
Broadly speaking, the subject of the Christology that is still worth talking about in the academic pulpit is the title